Role of Malondialdehyde Levels in The Occurrence of Hypogonadism in Transfusiondependent Thalassemia Male Patients - Lubis, Dian Anindita; Nasution, Melati Silvanni; Lubis, Heny Syahrini; Pohan, Hafiza Humayra Prabisma (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2024)
Male hypogonadism is a clinical syndrome resulting from the failure of the testes to produce adequate testosterone. Thalassemia major is an autosomal recessive disorder characterized by the absence or severe deficiency of the synthesis of the ÃŸ-globulin chain of hemoglobin that causes severe anemia requiring lifelong transfusions. Chronic blood transfusion in patients with ÃŸ-thalassemia leads to the accumulation of transfusion-associated iron in the tissues. Iron accumulation in the testes and pituitary gland generally leads to a state of hypogonadism. In patients undergoing repeated transfusions, there can be increased oxidative stress which can be assessed by examining malondialdehyde (MDA) levels. Increased oxidative stress can also affect a person's reproductive process through damage to pituitary tissue and LH hormones, which ultimately results in a decrease in a person's testosterone levels. Our aim is to see the correlation between malondialdehyde levels and free testosterone in male patients with transfusion-dependent thalassemia. This study used a cross-sectional design conducted at the Thalassemia polyclinic of RSCM and Fatmawati from January to March 2023. The study samples were transfusion-dependent thalassemia patients who met the acceptance criteria of the study subjects. Each patient underwent venous blood collection and was examined for serum ferritin levels, transferrin saturation, FSH levels, LH levels, free testosterone levels and MDA. The data obtained will be recorded and processed using the SPSS 20 program. Forty-one male subjects with transfusion-dependent thalassemia had a median free testosterone of 14.53 pg/mL (minimum-maximum 0.1-35.78). Twelve subjects (29%) of them had low testosterone levels. The median MDA level was 2.22 uM (0.18-2.61). There was no significant correlation between free testosterone and MDA (r=-0.18, p=0.261). There were high MDA levels in men with transfusion-dependent thalassemia. High MDA levels had no correlation with free testosterone in men with transfusion-dependent thalassemia.